New insights about the introduction of the Portuguese oyster, Crassostrea angulata, into the North East Atlantic from Asia based on a highly polymorphic mitochondrial region - Lallias, Delphine (2017)
It is commonly presumed that the Portuguese oyster Crassostrea angulata was introduced into the North East (NE) Atlantic from Asia. The analysis of the nucleotide sequence of a highly polymorphic non-coding mitochondrial region (major noncoding region - MNR) of C. angulata samples collected in Europe (Portugal), Africa (Morocco) and Asia (Shantou and Taiwan) provided new insight into the introduction of this species into the NE Atlantic. Sixty haplotypes and a nucleotide diversity of 0.0077 were observed in 130 analyzed sequences. Higher nucleotide diversity levels were observed in NE Atlantic sites than in Asian sites and significant genetic differentiation was found between the two. Our results suggest that C. angulata might have been introduced to the NE Atlantic by multiple introductory events, though the exact origins remain unknown since none of the analyzed Asian sites seemed to have been a source of introduction. The nucleotide diversity of C. angulata was higher than that previously reported for Pacific oyster C. gigas in Europe and Asia for the same mitochondrial region. The results obtained in the present study suggest that NE Atlantic C. angulata stocks are a unique genetic resource, which highlights the importance of their conservation.